2012
DOI: 10.1164/rccm.201011-1897ci
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Steroids in Severe Sepsis and Septic Shock

Abstract: Despite more than 5 decades of study and debate, the role of corticosteroid treatment in patients with severe sepsis and septic shock remains controversial. Data support a beneficial effect on systemic blood pressure in patients with septic shock. However, the ability of corticosteroid therapy to improve mortality in patients with severe sepsis and septic shock remains controversial, with contradictory results from recent large multicenter clinical trials. Although it appears clear that high-dose corticosteroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
99
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(108 citation statements)
references
References 56 publications
1
99
0
5
Order By: Relevance
“…In the subclass with suppressed glucocorticoid receptor signaling, corticosteroids were independently associated with greater mortality (46). This preliminary work provides a testable hypothesis of which patients with septic shock may benefit from corticosteroids, a therapy that remains controversial because of our current difficulty in identifying which patients will benefit (48).…”
Section: Identifying Biomarkers To Use For Predictive Enrichmentmentioning
confidence: 84%
“…In the subclass with suppressed glucocorticoid receptor signaling, corticosteroids were independently associated with greater mortality (46). This preliminary work provides a testable hypothesis of which patients with septic shock may benefit from corticosteroids, a therapy that remains controversial because of our current difficulty in identifying which patients will benefit (48).…”
Section: Identifying Biomarkers To Use For Predictive Enrichmentmentioning
confidence: 84%
“…Prophylactic intra-operative glucocorticoids did not benefit patients undergoing cardiac surgery [49]. Similarly, the role of steroids in sepsis remains unclear: while glucocorticoids improve vasopressor efficacy, it is uncertain whether they benefit patients [50]. No clinical study has specifically examined the impact of steroids on the glycocalyx in patients with sepsis.…”
Section: Damage To the Endothelial Surface Layermentioning
confidence: 99%
“…Although some randomized controlled trials have demonstrated mortality benefit with steroid therapy for patients in vasopressorunresponsive septic shock (hypotension despite fluid resuscitation and vasopressors for more than 60 min), other studies, including a large European multicenter trial (Corticosteroid Therapy of septic shock [CORTICUs]) failed to show a mortality benefit. 24 A review 25 on the use of steroids in adults with septic shock emphasized the importance of study selection for systematic analysis and confirmed the lack of evidence that the use of low-dose hydrocortisone improves the patients' outcome.…”
Section: Vasopressorsmentioning
confidence: 94%